O ensino de matemática para crianças com síndrome de Down: saberes teóricos e práticos nas séries iniciais do ensino fundamental - Silva, Mônica de Faria e (2020)
This research was made looking for an answer for the following question: How is the historical proceeding of Math teaching on the early grades of elementary school and what are the possible teaching strategies to develop the educational activities along with Down Syndrom kids? Facing this problem, this research had the objective of studying and recognizing the historical process of math teaching on starting years of school, aiming to propose educational strategies that will support the learning of these children; which led us to investigate the historical mathematics teaching and learning process; discuss the path of special needs education focusing on Down Syndrom children and identify potential strategies and methodologies to the mathematics teaching process for these kids. To fully achieve the objectives and to answer the proposed questioning, a bibliographic research was made through the approach of scientific publications on the chosen topics, in a qualitative approach, to identify how the contemporary researchers are treating the proposed subject-matter, starting specially at 2008 (with the Rights of the Disabled People Convention), in the field of inclusive education. The few researches found approaching this specific subject are geared towards the medical, nursing or general health professionals area (speech therapists, psychologists etc.). These researches, as a rule, emphasize the genetic and physical conditions, along with their consequences for the growth and development of the person with Down Syndrome. However, few focus on the school teaching and learning. This proves the necessity of the present research as a way to heal a scientific gap, seeking to be another contribution for studies and researches, with regard to education for this student.